MaxEnt modelling for risk assessment of soybean downy mildew, Peronospora manshurica in the Indian subcontinent - Anitha, K; Rameash, K; Sivaraj, N; Chakrabarty, S K; Kumar, G Suresh; Babu, B Sarath (Indian Journal of Plant Protection, 2020)
Soybean downy mildew, caused by Peronospora manshurica (Naum.) Syd., is an important pest of quarantine significance to India. As the disease occurrence from different countries across the globe is being reported year after year, there is a dire need to first assess its potential for establishment and spread in the country to formulate suitable strategies to contain the disease. In this regard, efforts have been made to identify potential regions likely to be affected in case of its inadvertent introduction into the country using maximum entropy-based (MaxEnt) modelling based on current world distribution data. For this, 19 bioclimatic variables available from the Worldclim website were used to assess the probability of soybean downy mildew presence in India. It can be inferred from the MaxEnt climate suitability modelling that the states in north (Jammu and Kashmir, Himachal Pradesh, Uttarakhand) and north-eastern India are likely to be affected by the soybean downy mildew and accordingly, suitable quarantine measures need to be put in place by relevant agencies concerned.